Interaction with virtual 3D port terminals using Unity3D - Tan, Raynold Yan Xian (Nanyang Technological University, 2021)
The upcoming Tuas Mega Port in Singapore is aiming to be the world’s largest fully automated terminal. However, it will only be fully constructed by 2040. Additionally, the only depictions of it are static renders which provide little information to its modern features. The aim of this project is to create a virtual 3D simulation of an automated port. The application will allow users to explore the features of a next-generation port. The simulation was created using the Unity3D game engine. It was assessed using software quality attributes, from the ISO 25010 software quality model, such as correctness, efficiency, usability and portability. After being assessed, the application was found to be slightly lacking in the usability attribute but is sufficient in all others. The project has fulfilled its requirements specified and is able to show users some features of the new port. Improvements can be done on the lack of instructions or tutorial, and use of placeholder models due to the lack of proper 3D models. For future similar projects, the automation of the port could be improved upon. This can be done by creating an importing and exporting of containers system where the containers would automatically be hauled from ships to storage and vice versa.